Amygdalin Promotes Fracture Healing through TGF-β/Smad Signaling in Mesenchymal Stem Cells - Jun Ying; Qinwen Ge; Songfeng Hu; Cheng Luo; Fengyi Lu; Yikang Yu; Taotao Xu; Shuaijie Lv; Lei Zhang; Jie Shen; Di Chen; Peijian Tong; et al. (Hindawi Limited, 2020)
Chondrogenesis and subsequent osteogenesis of mesenchymal stem cells (MSCs) and angiogenesis at injured sites are crucial for bone fracture healing. Amygdalin, a cyanogenic glycoside compound derived from bitter apricot kernel, has been reported to inhibit IL-1β-induced chondrocyte degeneration and to stimulate blood circulation, suggesting a promising role of amygdalin in fracture healing. In this study, tibial fractures in C57BL/6 mice were treated with amygdalin. Fracture calluses were then harvested and subjected to radiographic, histological, and biomechanical testing, as well as angiography and gene expression analyses to evaluate fracture healing. The results showed that amygdalin treatment promoted bone fracture healing. Further experiments using MSC-specific transforming growth factor- (TGF-) β receptor 2 conditional knockout (KO) mice (Tgfbr2Gli1-Cre) and C3H10 T1/2 murine mesenchymal progenitor cells showed that this effect was mediated through TGF-β/Smad signaling. We conclude that amygdalin could be used as an alternative treatment for bone fractures.